2020
DOI: 10.1016/j.numecd.2019.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the heterogeneity of the effects of SGLT-2 inhibitors in cardiovascular outcome trials

Abstract: Background and aim: The interpretation of discrepancies across cardiovascular safety trials (CVOT) with SGLT-2 inhibitors in the incidence of major cardiovascular events (MACE) and mortality is complex, because of heterogeneity in trial protocols and baseline characteristics of patients enrolled. Aim of this analysis is the exploration of possible determinants of heterogeneity of relative risk reduction for major cardiovascular events (MACE) and all-cause mortality. Methods and results: Incidence of events (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Despite apparently different results in trials with different molecules, the analysis of RCTs with GLP‐1 RA did not show any relevant heterogeneity. For both drug classes, the risk reduction of MACE was also associated with a significant reduction in all‐cause mortality, thus confirming previous results 9,12,51 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite apparently different results in trials with different molecules, the analysis of RCTs with GLP‐1 RA did not show any relevant heterogeneity. For both drug classes, the risk reduction of MACE was also associated with a significant reduction in all‐cause mortality, thus confirming previous results 9,12,51 …”
Section: Discussionsupporting
confidence: 89%
“…For both drug classes, the risk reduction of MACE was also associated with a significant reduction in all-cause mortality, thus confirming previous results. 9,12,51 There are two other therapeutic options, besides GLP-1 RA and SGLT2i, which are associated with a significant reduction in the risk of 3-point MACE: metformin and pioglitazone. Metformin had already been associated with a reduction of MACE, 15,52 whereas results on pioglitazone were contrasting.…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the fact that patients in the EMPA-REG OUTCOME study had a higher risk of death at baseline and the management used was secondary prevention. In contrast, in the other two studies, patients without CVD required a longer observation time before the beneficial effects of treatment became apparent [27].…”
Section: Sglt2 Inhibition and Clinical Outcomesmentioning
confidence: 91%
“…Further disparities between these studies may also result from different clinical characteristics of the patient populations studied (in the EMPA-REG OUTCOME trial only patients with confirmed CVD, and in other studies patients both with and without confirmed CVD) [27]. Such a difference explains the period of time taken for divergence of the lines illustrating mortality in the studied groups.…”
Section: Sglt2 Inhibition and Clinical Outcomesmentioning
confidence: 98%
See 1 more Smart Citation